Climate variability and incidences on agricultural production in the municipalities of Dassa-Zoume and Glazoue in the center of Benin - KADJEGBIN, TOUNDÉ ROMÉO GISLAIN; EGBETOWOKPO, Kokou; GUEDENON, Patient; HOUSSOU, CHRISTOPHE SÈGBÈ (My University, 2014)
The present work studies climate variabilities and theirs incidences on the agricultural production in Municipalities of Dassa-Zoumé and Glazoué. It is based on the analysis of thermal pluviometric data of the insolation, and the climate balance assessment, in order to estimate the climate characteristics on the agricultural production in Municipalities of Dassa-Zoumé and Glazoué. The methodological approach consisted in the calculation of climate parameters. The results revealed a very large variability of the rainfall from one station to another and that this significant variation of the precipitation represented a disruptive factor for the agricultural activities. The monthly average values of the calculated temperatures showed a variation between 25 and 30.5°C with effects on respiration and photosynthesis of plants therefore triggering a regression of the activities of agricultural production.
Keywords: Climate variabilities; incidences; agricultural production; Municipalities of Dassa-Zoumé and Glazoué.